Developing and validating a multi-dimensional scale for freshness perception of home air-care products - Yang, Gongshun (My University, 2025)
Freshness is a complex concept that encompasses both physiological and psychological dimensions. The goal of this dissertation is to develop and validate a standardized scale that measures consumer perceptions of freshness in home fragrances comprehensively, addressing a major gap in understanding freshness perception across different contexts and products. In the first phase, a qualitative approach was used to explore consumer terminology that contributes to freshness perception of home fragrances. Focus groups and E-commerce comment reviews helped identify key dimensions of freshness, including emotional and psychological factors, environmental elements, physical sensations, product context, and functional roles. These findings provide an understanding of how freshness is experienced by consumers, emphasizing aspects such as comfort, air quality, and lightness of scent. In the second phase, the scale was refined through a national survey. Factor analysis was used to ensure reliability and validity. Results confirmed four key dimensions of freshness perception such as environmental functionality, personal productivity, contextual associations, and emotional nostalgia. These dimensions had high internal consistency indicated by Cronbach’s alpha and highlight the importance of emotional, sensory, and environmental attributes in shaping consumers' understanding of freshness in home fragrances. In the third phase, the validated freshness scale was used in the context of product usage to determine its effectiveness in capturing consumer perceptions of home fragrances. The effectiveness of the freshness scale was further demonstrated. The findings showed that freshness involves more than just a pleasant fragrance; it also contributes to creating a cleaner, more comfortable environment. A Linen Clean scent, which enhances cleanliness and comfort perception, was rated as the most “fresh”. The results suggest that product development may focus on both sensory and environmental aspects to better meet consumer needs and expectations
Keywords: Freshness perception; Consumer psychology; Scale development; Sensory evaluation